Retos y oportunidades en la aplicación del Código de Conducta de la CNUDMI para árbitros en la solución de controversias internacionales relativas a inversiones - Ampuero Llerena, Ricardo Manuel (2025)
This article analyzes the UNCITRAL Code of Conduct for Arbitrators in International Investment Dispute Resolution in 2023. Based on a conceptual and regulatory review, it addresses key aspects of the instrument, such as the duty of continuous disclosure and restrictions on the simultaneous exercise of multiple roles (double hatting), along with an analysis of emblematic cases that reveal the importance of these rules. While the Code represents a step toward greater transparency and security, its implementation poses significant challenges, such as its coordination with existing regulatory frameworks, potential tensions with party autonomy, and uncertainty regarding the effectiveness of mechanisms to monitor compliance. In Latin America, and especially in Peru, its adoption could require institutional and regulatory adjustments to avoid an excessive reduction in the number of available professionals, allowing for the consolidation of a more accessible, representative, and reliable system.